2018
DOI: 10.1021/acs.jpcc.8b07826
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Transition from Solid-State to Molecular-Like Optical Properties in Ultrasmall Silicon Carbide Nanoparticles

Abstract: We employ time-dependent photoluminescence (PL) and steady-state PL excitation (PLE) measurements to study the size-dependent optical properties of ultrasmall silicon carbide (SiC) nanoparticles (NPs). We find that the nature of the optical transition transforms from solid-state indirect gap to molecular-like as the diameter of spherical SiC NPs is reduced from 4–6 to 1–3 nm with a smooth transition in between. We deduce the radiative lifetimes of SiC NPs that are well supported by ab initio time-dependent den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…SiC NPs with different diameters, namely, ultrasmall (ø = 1–3 nm) and larger SiC NPs (ø = 4–6 nm), were synthesized in our laboratory, and the synthesis and properties, as a function of size, can be found in our previous reports. 23 , 38 , 39 …”
Section: Experimental Sectionmentioning
confidence: 99%
“…SiC NPs with different diameters, namely, ultrasmall (ø = 1–3 nm) and larger SiC NPs (ø = 4–6 nm), were synthesized in our laboratory, and the synthesis and properties, as a function of size, can be found in our previous reports. 23 , 38 , 39 …”
Section: Experimental Sectionmentioning
confidence: 99%
“…On the other hand, the sp 2 -carbon at the SiC surface can improve the specific contact resistance of the SiC/metal interface . The surface of SiC accommodates diverse surface reconstruction and termination with corresponding defects such as bridge and triple-bonded C/Si dimers, which generate fruitful surface states in the band gap. Hence, the SiC surface has attracted great interest. , As the dimension of the semiconductor SiC is reduced to the nanoscale, its surface structure becomes even more complex, the dangling bonds of the active carbon and silicon atoms of the freshly prepared SiC quantum dots (QDs) can readily be passivated by oxygen and hydrogen atoms to form quite fruitful bonding structures. The resultant surface states in the band gap can actively participate in the photon absorption and emission processes. The whole surface passivation layer becomes a two-dimensional quantum system, which in combination with quantum confinement and the intentionally created interior point defects determines the photodynamics , and charge transport properties of the SiC QDs. Therefore, understanding the surface structures and characteristics of the SiC QDs is critical for realizing their better applications in biological labeling, solid-state lighting, and quantum spintronics. Our previous study indicates that the CO bonds on the SiC QD surface generate surface-localized orbitals and contribute to the blue fluorescence; however, the role of the silicon–oxygen bonds in fluorescence of the SiC QDs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SiC QDs can be used as stable light sources for sensors, cell imaging, and light‐emitting diodes . On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence . The study had indicated that for the SiC QDs smaller than 1 nm, the surface defect‐related luminescence dominates .…”
Section: Introductionmentioning
confidence: 99%